2014
DOI: 10.1002/sca.21142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the shear bond strength of resin cement to Y‐TZP ceramic after different surface treatments

Abstract: The purpose of this study was to evaluate the effect of various surface treatments on the shear bond strength of Y-TZP (Yttria-Tetragonal Zirconia Polycrystal) ceramics with zirconia primer and two different resin cements both containing 10-methacryloyloxydecyl dihydrogen phosphate (MDP). Zirconia blocks (LAVA, 3M ESPE, St. Paul, MN) were polished and assigned to five groups according to the surface treatment: (1) no further treatment (control); (2) airborne abrasion with Al2 O3 particles; (3) Z-PRIME Plus (Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
71
1
25

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 40 publications
13
71
1
25
Order By: Relevance
“…In a µTBS test, the weakest part should be the part that fractures. In this context, evaluation of mechanical strengths of the adhesive resin cement correlates to bond strength 18) . In general, 10-MDP containing adhesives have always demonstrated good bonding performance in laboratory and clinical research environments 19,20) .…”
Section: Discussionmentioning
confidence: 99%
“…In a µTBS test, the weakest part should be the part that fractures. In this context, evaluation of mechanical strengths of the adhesive resin cement correlates to bond strength 18) . In general, 10-MDP containing adhesives have always demonstrated good bonding performance in laboratory and clinical research environments 19,20) .…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, esta reação química não é aplicável às cerâmicas à base de zircônia devido à ausência de sílica. 8,[10][11][12][13] O tratamento de superfície ideal para as cerâmicas à base de zircônia é motivo de apreensão até os dias atuais. Não há unanimidade quanto ao melhor condicionamento superficial e inúme-ros tratamentos de superfície têm sido descritos na literatura para cerâmicas à base de zircônia.…”
Section: Revisão Da Literatura/discussãounclassified
“…16 No entanto, o jateamento induz a transformação da fase tetragonal para a fase monoclínica, desencadeando a propagação de microfissuras na cerâmica durante a função e isso diminui o desempenho a longo prazo da restauração em cerca de 20 a 30%. 2,6,[8][9][10]15,17,18 Shin et al 11 avaliaram o efeito de diferentes tratamentos de superfície sobre a força de união de dois diferentes cimentos resinosos contendo monômeros fosfatados à uma cerâmica à base de zircônia. Os autores concluíram que o jateamento com partículas de óxido de alumínio seguido da aplicação de um primer para zircônia alcançou o melhor resultado de união.…”
Section: Revisão Da Literatura/discussãounclassified
See 1 more Smart Citation
“…Published papers have shown that establishing a chemical bond with zirconia is difficult, which open the door to investigations on different surface treatments. [12][13][14][15][16] Zirconia…”
Section: Introductionmentioning
confidence: 99%